The Application of Al-Wakalah bil Ujrah Contract on Unit Link Insurance According to DSN-MUI Fatwa No. 52 2006: A Case Study of PRUlink Syariah Generasi Baru - Fadhila Sukur Indra; Sahira Sajjadia Luthia; Andini Rachmawati; Arif Dian Santoso; Devid Frastiawan Amir Sup (Department of Islamic Economics, Islamic University of Indonesia, 2022)
Insurance makes the fund prepared accurately when problems or disasters occur without predictions. Also, in sharia insurance, there is al-wakalah bil ujrah which is used to give authority to manage the premium collected funds so that they can be useful and develop. This study aims to determine how the application of the al-wakalah bil ujrah contract on PRULink Syariah Generasi Baru at PT Prudential Indonesia. Then, to find out the level of validity according to the Fatwa DSN-MUI No: 52/DSN-MUI/III/2006 concerning al-Wakalah bil Ujrah Contract on Sharia Insurance and Reinsurance. This study uses a qualitative method in field research and a descriptive analysis approach. Data collection was carried out through field observations, interviews with related sources, and documentation which was analyzed using the measurement tool to DSN-MUI Fatwa No: 52/DSN-MUI/III/2006. The results shows that Prudential Syariah Yogyakarta Branch sufficiently met the criteria set by the DSN-MUI Fatwa No: 52/DSN-MUI/III/2006 concerning al-wakalah bil ujrah Contract on Sharia Insurance and Reinsurance. All provisions are written and explained at the beginning of the contract, although not all mechanisms are included in the company standard, such as the accuracy of the allocation of investment funds that distributed to the stock market, the criteria for insurance participants who do not meet the requirements surplus sharing and the lack of transparency in the management of tabarru' funds.